Training process individualizing by athlete-coach-psychologist triad synergy - Vyatkin, B. A.; Markelov, V. V.; Sysoev, Yu. V.; Kraev; Yu. V. (Theory and Practice of Physical Culture, 2019)
The article analyzes the ways to individualize and harmonize the training process by the synergy of athlete, coach and psychologist as the key process actors; applies the individuality integration theory to design the synergized triune cooperation model to efficiently mobilize the individual creative resources; and outlines the key avenues for the individualized training service to secure good progress with every domain of an integrated individuality being activated and harmonized. Methods and toolkit of the synergized triune cooperation model are geared to help every actor concentrate on the self-improvement, self-exploring, self-identification, self-control and self-integration goals to efficiently contribute to the training process efficiency. The prudent integration and individualization of the triune efforts will help design an individual progress strategy for every athlete and mobilize, on a systemic, synergized and mental conditioning prioritizing basis, creative resource for success of the teamwork.